Adherence of Public Officials to the Disclosure of Conflict of Interest While Performing Their Job Responsibilities: A Comparative Study between French and Jordanian Law - Hadeel Tayseer Mahmoud Al-Zu’bi (دراسات: علوم الشريعة والقانون, 2024)
Objectives: This study aims to analyze the legal framework regarding the duty of public officials to disclose conflicts of interest and draw lessons from the French experience. It identifies legislative gaps in Jordanian laws concerning the duties of public officials, the nature of conflicts of interest, and the mechanisms for disclosure during and after service.